The Role of Slum Tourism in Sustainable Urban Development of Slum Areas in Iraq - Al-Taee Omaima; Jaleel Ameera (Civil and Environmental Engineering)
The concept of sustainable development has occupied the attention of the international community to meet the growing challenges of urban growth and population growth in the 21st century. The phenomenon of slums is one of the most important of these challenges, on the other hand, slum tourism has emerged as a solution to these challenges, as it is considered an engine of economic growth, cultural communication, and social interaction, and has become a legitimate global tourism that attracts nearly one million tourists annually. Iraq suffers from spread of slums around cities with a clear shortage of tourist facilities; difficult access; loss of security and safety; weak marketing and promotion; and the need for organization and integrated management. The research is an attempt to fill the need for knowledge about the role of urban catalyzation strategies in activating this type of tourism and achieving sustainable development of slums, and to achieve the objectives of the research, an inductive analytical approach was used to collect and analyze data from previous literature, and a field survey was conducted for a random sample (150 people) from the local community with interviews with residents and analysis of global applications, to identify the extent of the local community’s knowledge of the concept of slum tourism and its role in achieving sustainable urban development for these areas. The research found that slum tourism plays an important role in achieving sustainable urban development for these areas, as it contributes to the economic growth of local communities, reduces poverty, reduces the negative impact on the environment and accelerates the growth and development of local areas in general.